Botulinum Neurotoxin A Injected Ipsilaterally or Contralaterally into the Striatum in the Rat 6-OHDA Model of Unilateral Parkinson’s Disease Differently Affects Behavior - Antipova, Veronica A.; Holzmann, Carsten; Schmitt, Oliver; Wree, Andreas; Hawlitschka, Alexander (Frontiers in Behavioral Neuroscience, 2017)
Parkinson's disease (PD) is one of the most frequent neurodegenerative disorders. The loss of dopaminergic neurons in the substantia nigra leads to a disinhibition of cholinergic interneurons in the striatum. Pharmacotherapeutical strategies of PD-related hypercholinism have numerous adverse side effects. We previously showed that ipsilateral intrastriatal injections of 1 ng in unilaterally 6-hydroxydopamine (6-OHDA)-lesioned rats inhibit apomorphine-induced rotation behavior significantly up to six months. In this study we extended the behavioral testing of ipsilateral BoNT-A-injection and additionally investigated the impact of intrastriatal BoNT-A-injections contralateral to the 6-OHDA-lesioned hemisphere on the basal ganglia circuity and motor functions. We hypothized that the interhemispheric differences of acetylcholine concentration seen in unilateral hemi-PD should be differentially and temporally influenced by the ipsilateral or contralateral injection of BoNT-A. Hemi-PD rats were injected with 1 ng BoNT-A or vehicle substance into either the ipsilateral or contralateral striatum 6 weeks after 6-OHDA-lesion and various behaviors tested. In hemi-PD rats intrastriatal ipsilateral BoNT-A-injections significantly reduced apomorphine-induced rotations and increased amphetamine-induced rotations, but showed no significant improvement of forelimb usage and akinesia, lateralized sensorimotor integration and also no effect on spontaneous locomotor activity. However, intrastriatal BoNT-A-injections contralateral to the lesion led to a significant increase of the apomorphine-induced turning rate only two weeks after the treatment. The apomorphine-induced rotation rate decreases thereafter to a value below the initial rotation rate. Amphetamine-induced rotations were not significantly changed after BoNT-A-application in comparison to sham-treated animals. Forelimb usage was temporally improved by contralateral BoNT-A-injection at two weeks after BoNT-A. Akinesia and lateralized sensorimotor integration were also improved, but contralateral BoNT-A-injection had no significant effect on spontaneous locomotor activity. These long-ranging and different effects suggest that intrastriatally applied BoNT-A acts not only as an inhibitor of acetylcholine release but also has long-lasting impact on transmitter expression and thereby on the basal ganglia circuitry. Evaluation of changes of transmitter receptors is subject of ongoing studies of our group.